Psychological Factors on Students’ Speaking Skill Problems at Junior High School - Rara Dewi Putri Rahmadani; Yuli Astutik; Endang Mastuti Rahayu (Tell : Teaching of English Language and Literature Journal, 2024)
There are several psychological factors that can affect the development of students' speaking skills in English. This study was conducted with the aim of finding out what psychological factors affect the development of students' speaking skills in English when learning speaking in class. This research uses descriptive qualitative method, where data collection was carried out through observation and interview with some private junior high school students in grade 7 with ICO (International Class Orientation) class program. The results of this study show that there are four factors that can hinder students in developing and also mastering speaking skills, namely anxiety or shyness, lack of confidence, lack of motivation, and fear of making mistakes. These four psychological factors have a negative impact on students during the speaking learning process. Therefore, the findings of this study imply that parents and teachers should help students understand that making mistakes is a necessary part of learning and that they can take advantage of these opportunities to grow as communicators. In order to give students the chance to practice speaking English without worrying about making mistakes, the teacher must also foster a supportive environment in the classroom.